Association of Pro Protein Convertase Subtilisin / Kexin 9, Apo B and HbA1c in Coronary Artery Disease with and without Diabetes Mellitus: Life Sciences-Biochemistry - P K, Deepa; G S R, Kedari; C R1, Resmi (International Journal of Life Science and Pharma Research, 2022)
Pro-protein convertase subtilisin/Kexin type 9 (PCSK9) is a soluble protein synthesized as a zymogen that influences plasma levels of low-density lipoprotein cholesterol (LDL-C). Understanding the association is very essential to develop adequate treatment strategies. Hence,the present study aims to explore the relationship between plasma levels of PCSK9, Apo B, and HbA1C in patients with coronary artery disease (CAD) with Diabetes Mellitus. All patients had no history of using lipid-lowering medication. Of these 62patients (40 male and 22 female, age group 30 -70 years), all had angiographically diagnosed CAD.25 are CAD with DM, and 37 are CAD without DM. Plasma PCSK9 and Apo B were measured using an enzyme-linked immunosorbent assay (ELISA). HbA1 c Levels are measured by using the HPLC method. In this work, we compared plasma PCSK9 and Apo B in CAD with DM and CAD without DM with the help of the HbA1c value. Both plasma levels of PCSK9 (0.040 (<0.050) and 0.036 (<0.05)) and Apo B (0.021 (< 0.05) and [(0.425 (> 0.05)] HbA1C were significantly higher in patients with CAD and DM as compared with those with CAD without DM. In Group with CAD without DM there is no elevation of HbA1C but PCSK 9 and Apo B are significantly elevated. PCSK 9 and Apo B are independent markers of CAD. Correlation analysis showed plasma level of PCSK9 was significantly correlated (P<0.05) with that of Apo B in both patients with CAD and without DM. However, multivariate regression analysis after adjustment for age, gender, smoking, alcohol, hypertension, and hyperlipidemia showed that only in CAD patients with diabetes mellitus, there was a significant positive correlation (p<0.05) between plasma levels of PCSK9 and HbA1C.